(untitled) - Richter-Addo, George B (Oxford, 1992)
This book covers all aspects of metal-nitric oxide chemistry. Topics range from descriptions of the metal-NO bond to their chemical reactions and environmental significance. Treated in detail are coordination and organometallic nitrosyl complexes, interactions of nitric oxide with surfaces, metal nitrosyl clusters and the biosynthesis, biotransformation, and bioinorganic chemistry of nitric oxide. The book includes an examination of all known classes of reactions of metal nitrosyls. The roles of nitric and nitrous oxides in environmental chemistry are outlined in the closing chapter. This book will be of interest to students and researchers in the fields of inorganic, organometallic, and bioinorganic chemistry.
Keywords: Nitroso compounds,Organometallic compounds